The Dynamics of Harmony Among Religious Communities in Southeast Aceh Regency: Challenges and Development Strategies - Faizal Lukman; M. aditya prayoga; M. Syukri Riski Hamdalah (Al Mabhats : Jurnal Penelitian Sosial Agama, 2025)
This study discusses the dynamics of interfaith harmony in Aceh Tenggara Regency, which has diverse ethnic and religious backgrounds. As a region characterized by cultural and religious pluralism, Aceh Tenggara faces challenges in maintaining harmony among adherents of different faiths. The aim of this research is to identify the challenges faced, as well as the fostering strategies implemented by the government and the community to enhance interfaith harmony. The methodology employed in this study is qualitative-descriptive with a field study approach. Data were collected through interviews, observations, and literature reviews. The findings indicate that interfaith harmony in Aceh Tenggara encounters several challenges, including differing religious interpretations, social-economic conflicts of interest, and a lack of cross-cultural understanding. To address these challenges, the government and religious leaders have implemented various fostering strategies such as interfaith dialogue forums, joint social activities, and multicultural education in schools. These findings provide insights into the importance of participatory approaches in fostering harmony, as well as the necessity for support from all elements of society to create a harmonious social climate in Aceh Tenggara.